Phonological Interference and Morphology of BMT in Student Narrative Essays, Indonesia - Irmayani Putri; Syahnan Daulay; Malan Lubis (BIRCU, 2019)
This Study dealt with Morphology of BMT in Student Narrative Essays, Indonesia In Tamiang Dialect. The influence of the downstream dialect language of Tamiang cannot be ignored by the people of Tamiang Hilir. The Lower dialect Tamiang language used since childhood in the home, family environment, and the community has been so pervasive to the users of the local language. This fact shows that the people of Tamiang Hilir often use Indonesian in a formal environment or only certain circles. The method used in this research is descriptive qualitative method. Qualitative research generally tries to form or construct theory through collected data. In the description, it is presented in a systematic, factual, and accurate manner regarding the data and characteristics of the phenomena studied. The result shows that There are phonological equations, morphology in Malay and Indonesian. Because, Indonesian root groups adopted the Malay language as the basis for use. So that many lexical meanings are homonym, homograph and hyponym in Malay that are similar to Indonesian and other regional languages.